Absence of high-grade cervical intraepithelial neoplasia in conization specimens from patients with colposcopic biopsy-confirmed high-grade cervical intraepithelial neoplasia: Retrospective study of 1695 cases - Guo, Yulin; Wang, Ying; Peng, Qiuzi; Li, Lu; Zou, Miao; Wang, Chaonan; Wu, Xufeng; Ma, Quanfu (Frontiers in Oncology, 2022)
Background: Few studies have investigated the absence of high-grade cervical intraepithelial neoplasia (CIN) in excised specimens, and sample sizes of these studies were limited. Objective: This study retrospectively analyzed clinical characteristics of 1695 patients with CIN 2/3 to determine the incidence rate and relative factors of CIN 1 or less in conization specimens from patients with colposcopic biopsy-confirmed CIN 2/3. Methods: The study group comprised 430 cases of CIN 1 or less in conization specimens, and the control group comprised 1142 cases with high-grade CIN lesions in conization specimens. Univariate and multivariate logistic regression models were established to evaluate relative factors. The 1–9 years follow-up data were analyzed to determine the persistence/recurrence rate. Results: Multivariate logistic regression showed that patients aged 18–24 years (OR (95% CI) = 2.224 (1.014, 4.877)); with a negative hrHPV test result (OR (95% CI) = 3.210 (1.627, 6.331)); a cytology test result of normal (OR (95% CI) = 5.184 (3.138, 8.563)), ASC-US (OR (95% CI) = 3.420 (2.102, 5.564)), LSIL (OR (95% CI) = 2.588 (1.475, 4.541)), or ASC-H (OR (95% CI) = 2.434 (1.306, 4.539)); an indication of CIN 2 on biopsy (OR (95% CI) = 2.290 (1.694, 3.096)), and no glandular involvement (OR (95% CI) = 1.616 (1.205, 2.169)) were more likely to have an absence of high-grade dysplasia in conization specimens. There was no difference in the persistence/recurrence rate between the two groups (x2 = 1.55, P = 0.46). Conclusions: An age of 18–24 years, a negative hrHPV test result, a non-HSIL cytology test result, an indication of CIN 2 on biopsy, and no glandular involvement were relative factors for an absence of high-grade dysplasia in conization specimens. For patients with relative factors, especially young women, informed follow-up should be considered.